FRI0341 Do Patients with SLE at Onset Differ from Mimickers? A Comparison of Clinical and Serological Manifestations in A Multicenter Cohort To Inform The Development of New Classification Criteria for SLE. (15th July 2016) - Touma, Z.; Costenbader, K.H.; Johnson, S.; Mosca, M.; Hoyer, B.F.; Navara, S.; Bonfa, E.; Ramsey-Goldman, R.; Medina-Rosas, J.; Tani, C.; Fine, A.; Tedeschi, S.; et al.
Abstract : Background: Current SLE classification criteria may not classify patients with early SLE well. SLE mimickers can have an initial presentation similar to SLE and need to be distinguished from early SLE patients by classification criteria. Objectives: To describe the clinical and serological presenting manifestations of SLE at disease onset and those of SLE mimickers. Methods: We collected clinical and laboratory data on patients newly presenting with potential SLE (symptoms <12 months) within the past 3 years at centers in Europe (2), North America (3), South America (1) and Asia (1). Patients were diagnosed as SLE or mimicking conditions by clinical experts. We compared the presenting manifestations in SLE vs. mimickers. We examined combinations of autoantibodies, clinical and laboratory manifestations for their association with SLE vs. SLE mimickers in multivariable analyses. Results: Of 616 patients, 389 were diagnosed with SLE (89% female) and 227 were given other diagnoses (97% female). A smaller proportion of SLE patients than patients with mimicking conditions were White (55% vs. 90%). Mimickers included UCTD, Sjögren's syndrome, rheumatoid arthritis, scleroderma, and fibromyalgia. Clinical and autoantibodes presenting manifestations in new onset SLE and mimickers are represented in table 1 . In univariable analyses, the following autoantibodies profiles were associated with SLE vs. mimickers: Profile 1 (ANA, anti-Sm, anti-Ro and anti-RNP; OR 3.49, 95% confidence interval [CI] 2.29–5.31) and Profile 2 (ANA, anti-cardiolipin IgG/IgM, Beta2 and lupus anticoagulant; OR 2.82, 95% CI 1.75–4.55). In multivariable analyses, the following autoantibodies profiles were associated with SLE vs. mimickers: Profile 1 (OR 3.02, 95% CI 1.90–4.80) and Profile 2 (OR 3.11, 95% CI 1.80–5.36). Adding hypocomplementemia to Profile 1 and 2 showed a high association with SLE [OR 3.40, 95%CI 2.21–5.22 and OR 2.41, 95%CI 1.53–3.80] respectively. Conclusions: We identified clinical manifestations and autoantibodies more commonly associated with SLE than with mimickers at initial presentation. Autoantibody profiles particularly including ANA and especially in the presence of hypocomplementemia, showed associations with SLE. Acknowledgement: New SLE classification criteria for clinical research are being developed, sponsored by EULAR and ACR. Disclosure of Interest: None declared